Peningkatan Hasil Belajar Sosiologi Dengan Model Pembelajaran Scramble - Sri Devi Ayuni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2024)
This research aims to improve sociology learning outcomes at MAN Kupang City by applying the scramble learning model. This research is classroom action research (PTK) intended to overcome problems in the classroom. The subjects of this research were students in class X IIS2 MAN Kupang City, totalling 29 students. This research was carried out in each cycle with two meetings. Data collection techniques in this research used observation sheets, interviews and test sheets. The data analysis techniques used are qualitative and quantitative analysis. The results of the research showed that the initial test had an average of 79.2 and experienced an increase in cycle I with an average evaluation of learning outcomes of 17.24, and observation of learning outcome indicators with an average of 86.19 and experienced an increase in cycle II in evaluation results with an average of 96.54. These results include the classical completeness target of 80%.